The interactive multimedia video article: An Innovative Format for the Scientific Community (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2020)
The study explains the creative process to compose an innovative scientific communication product: Interactive Multimedia Video Article. The result is a pilot product based on the IMRaD research format and represents an alternative to the traditional research article.
Keywords: Scientific communication; video article,; IMRaD; e-learning; audiovisual production